The impact of hypsarrhythmia on infantile spasms treatment response: Observational cohort study from the National Infantile Spasms Consortium. (3rd November 2017) - Demarest, Scott T.; Shellhaas, Renée A.; Gaillard, William D.; Keator, Cynthia; Nickels, Katherine C.; Hussain, Shaun A.; Loddenkemper, Tobias; Patel, Anup D.; Saneto, Russell P.; Wirrell, Elaine; Sánchez Fernández, Iván; Chu, Catherine J.; et al.
Summary: Objective: The multicenter National Infantile Spasms Consortium prospective cohort was used to compare outcomes and phenotypic features of patients with infantile spasms with and without hypsarrhythmia. Methods: Patients aged 2 months to 2 years were enrolled prospectively with new‐onset infantile spasms. Treatment choice and categorization of hypsarrhythmia were determined clinically at each site. Response to therapy was defined as resolution of clinical spasms (and hypsarrhythmia if present) without relapse 3 months after initiation. Results: Eighty‐two percent of patients had hypsarrhythmia, but this was not associated with gender, mean age, preexisting developmental delay or epilepsy, etiology, or response to first‐line therapy. Infants with hypsarrhythmia were more likely to receive standard treatment (adrenocorticotropic hormone, prednisolone, or vigabatrin [odds ratio (OR) 2.6, 95% confidence interval (CI) 1.4–4.7] and preexisting epilepsy reduced the likelihood of standard treatment (OR 3.2, 95% CI 1.9–5.4). Hypsarrhythmia was not a determinant of response to treatment. A logistic regression model demonstrated that later age of onset (OR 1.09 per month, 95% CI 1.03–1.15) and absence of preexisting epilepsy (OR 1.7, 95% CI 1.06–2.81) had a small impact on the likelihood of responding to the first‐line treatment. However, receiving standard first‐line treatment increased the likelihood of responding dramatically: vigabatrin (OR 5.2, 95% CI 2–13.7), prednisolone (OR 8, 95% CI 3.1–20.6), and adrenocorticotropic hormone (ACTH; OR 10.2, 95% CI 4.1–25.8) . Significance: First‐line treatment with standard therapy was by far the most important variable in determining likelihood of response to treatment of infantile spasms with or without hypsarrhythmia.